Buddhism: a philosophical approach - Panjvani, Cyrus (Broadview Press, 2014)
"This book philosophically introduces the basic truths, doctrines, and principles of Buddhism. Its goal is to explain the teachings of the Buddha and of Buddhism clearly and consistently. Though the book treads beyond the Buddha's life, including into the Abhidharma and Mahayana traditions, it remains throughout a philosophical discussion and elaboration of the Buddha's thought. It is meant to be an accessible guide for those who have no background in Buddhism, and to be beneficial to the philosophical understanding of those who do."--Amazon.com summary